2017
DOI: 10.1038/s41598-017-08128-1
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Tumor-infiltrating Lymphocytes in Hepatocellular Carcinoma: a Systematic Review and Meta-analysis

Abstract: Previous clinical studies have found that the levels of tumor-infiltrating lymphocytes (TILs) significantly correlated with prognosis in hepatocellular carcinoma (HCC). However, these conclusions and data remain controversial. We performed a systematic review and meta-analysis to assess the prognostic value and clinical utilization of TILs in patients with HCC. A total of 23 relevant studies of 3173 patients were included into our meta-analysis. The results demonstrated that high levels of CD8+ and CD3+ TILs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 53 publications
6
101
1
Order By: Relevance
“…Tumorinfiltrating lymphocytes (TILs) may represent important antitumor effector cells associated with improved prognosis. (23) In the present study, the LMR decreased 1 month after LDLT in almost all of the patients, and the LMR increased again 1 year after LDLT. These findings indicate that immunosuppression after LDLT caused the decrease in LMR, and the reduction of immunosuppression 1 year after LDLT caused LMR to increase.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Tumorinfiltrating lymphocytes (TILs) may represent important antitumor effector cells associated with improved prognosis. (23) In the present study, the LMR decreased 1 month after LDLT in almost all of the patients, and the LMR increased again 1 year after LDLT. These findings indicate that immunosuppression after LDLT caused the decrease in LMR, and the reduction of immunosuppression 1 year after LDLT caused LMR to increase.…”
Section: Discussionsupporting
confidence: 64%
“…Generally, cytokines and chemokines produced by cancer cells reflect inflammation that occurs locally and systemically during cancer progression. Tumor‐infiltrating lymphocytes (TILs) may represent important antitumor effector cells associated with improved prognosis . In the present study, the LMR decreased 1 month after LDLT in almost all of the patients, and the LMR increased again 1 year after LDLT.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al found that CD8 + TILs were associated with improved DFS, while FOXP3+ TILs were associated with reduced DFS in breast cancer [54]. Yao et al reported that high levels of CD8 + and CD3 + TILs had a better prognostic value on OS and DFS, whereas high levels of FoxP3 + TILs had a worse prognostic value on OS and DFS [55]. In contrast, our study found that CD4 + had no prognostic value and high level of FOXP3 + TILs was associated with better DFS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to many cancers, HCCs do not generally down‐regulate HLA‐class I expression; HLA‐A is up‐regulated in 54% of patients . A recent meta‐analysis confirmed that high levels of HCC tumor infiltration by CD8 + T cells improved clinical outcomes, including overall survival . Several groups have isolated class I restricted tumor‐killing T‐cell clones that were generated spontaneously in HCC patients.…”
mentioning
confidence: 99%